Elements Men’s Rea and Inchoate Crimes (International Journal of Innovative Research in Engineering & Management, 2021)
The common law was slow to recognize attempted murder as a  crime. Early English law was founded on the premise that  attempting to injure someone was not a crime. Of process, if a  man damages someone in the process of attempting to kill him, he might be punished. But it was not a penalty for committing  a more severe crime, and it seems that if no bodily harm was  done as a result of the effort, no prosecution was conceivable  or considered appropriate: 'It was not until the fifteenth century  that the penal law was systematically expanded to attempted,  and only to committed offences, in the Tribunal of the Star  Chamber. According to the author, prosecuting crimes  frequently necessitates a sophisticated examination of  culpability in individuals who engage in organized criminal  activity. People have long been divided on whether or not a  person should be prosecuted for attempting to commit a crime  without actually committing one. It is claimed that the offenses  that the person wishes to perpetrate are of like a severe nature  that, even if the offense is not accomplished, prosecuting the  activities taken in the process of the offense is in the general  interests.
Keywords: Attempt; Crimes; Mens Rea; Law; Prosecution